Neutrons and model membranes: Moving towards complexity. (November 2018) - Fragneto, Giovanna; Delhom, Robin; Joly, Loïc; Scoppola, Ernesto
Abstract: Cells, the basic units of living organisms, are well delineated and separated from the external environment by membranes. Capable of both enclosing the cellular constituents and allowing exchanges with the outside world, these membranes are only a few nanometers thick. All the membranes in a human body cover an area of a few hectares, but account for only a small part of our mass. To study the dynamics and function of these amazing objects, physicists first seek to understand their structure. This involves experiments on model systems, simpler and better controlled than real membranes, and can profit from a probe that is able to access different scales of size and time: thermal neutrons. Since the pioneering work in the seventies on cell membrane structure by neutron scattering, developments driven by constantly improving neutron instrumentation, coupled with development of measurement and analysis methods, have involved both the optimization of samples towards more biologically relevant model systems and include the use of more complex lipid mixtures up to natural extracts. This review does not have the ambition to address the large number of contributions from all the groups working in this area in research laboratories and neutron facilities. It gives an update on some studies in the field carried out mainly by the authors and collaborators. Graphical abstract: Image 1 Highlights: Neutron scattering techniques are more and more popular for the study of the structure of biological membranes. Neutron scattering allows sub-nanometric characterization. Membranes have been prepared and characterised from natural lipid extracts.